The crested caracara (Caracara plancus) eye: Morphologic observations and results of selected diagnostic tests. (23rd September 2021) - Baldotto, Suelen Berger; Somma, André Tavares; Lange, Rogério Ribas; Machado, Marcello; Moore, Bret A.; Montiani‐Ferreira, Fabiano
Abstract: Purpose: To provide a descriptive investigation about relevant features of the crested caracara's eye ( Caracara plancus ) and bony orbit, as well as provide data for ophthalmic tests. Methods: Morphological observations and the following diagnostic tests were performed: Schirmer tear test (STT), conjunctival flora evaluation, corneal touch threshold (CTT), intraocular pressure (IOP), central corneal thickness (CCT), B‐mode ocular biometry, palpebral fissure length (PFL), and corneal diameter (CD) in 19 healthy birds, plus two macerated skulls. Not all birds were used for each test. Results: STT: 7.84 ± 3.05 mm/min; CTT: 2.46 ± 1.10 cm; IOP: 19.18 ± 3.07 mmHg; CCT: 0.31 ± 0.02 mm; PFL: 13.32 ± 1.06 mm; CD: 10.26 ± 2.43 mm; Axial globe length: 1.89 ± 0.06 cm; Anterior chamber depth: 0.27 ± 0.06 cm; Lens axial length: 4.55 ± 0.06 cm; Vitreous chamber depth: 1.2 ± 0.07 cm. The most frequent conjunctival bacterial isolates were Corynebacterium sp. (10/23.8%), Staphylococcus sp. (9/21.42%), Streptococcus sp. (7/16.6%), and E . coli (7/16.66%). The large lateral part of the palatine bone likely plays a role in the ventral protection of the globe against the impact of prey. Observed results are generally reflective of increased body mass compared to other Falconiformes, with values approaching those of similar sized Accipitriformes. Conclusions: These data may help veterinarians recognize peculiar morphologic features and perform a more accurate diagnosis of eye diseases of this avian species.